The future of the global agri-food trade and the WTO - Piñeiro, Valeria; Piñeiro, Martín (2017)
In recent years, the international trade context has seen, as a consequence of political changes, social unrest and violence, increased uncertainty and instability. Two main trends, one economic and one political, have affected the economic and political environment in which the evolution of the global trading system has been taking place.